THE ROLE OF BODY IMAGE AND PSYCHOLOGICAL FACTORS IN SHAPING THE SELF-IMAGE IN ADOLESCENCE (American Journal of Interdisciplinary Research and Development, 2026)
Adolescence is one of the most difficult and crisis periods in human development. At this stage, the intertwining of physiological changes and psychological searches directly affects a teenager's sense of self. The article scientifically differentiates teenagers' attitude to their appearance, the instability of the self-image and the dependence of their authority in the social environment on body image. The article examines the factors of "status uncertainty" and emotional instability in adolescence, the definition of "body image" and its connection with projection and self-esteem in the brain, the difference in the rate of physiological maturity in boys and girls and its impact on psychological adaptation, the influence of external beauty on social relationships and authority among peers. The importance of a subjective attitude to physical fitness in the formation of adolescents' self-esteem is also substantiated.